Factors affecting the thermal activation of Neosartorya fischeri in pineapple and papaya nectars - Slongo,Adriana Paula (2006)
In this research factors that influence the activation of Neosartorya fischeri ascospores (heating medium, temperature of production and age of the ascospores) were studied. The heating medium used was pineapple and papaya nectars at different ratios (ºBrix/acidity). Lower activation times were observed for the N. fischeri ascospores in pineapple and papaya nectars under the conditions of temperature and production age of 25ºC for 1 month and using ratios of the heating medium of 10 for pineapple nectar and 26 for papaya nectar. In these cases, the activation time was 5 minutes for the pineapple nectar and 10 minutes for the papaya nectar at 85ºC. For the ascospores produced at 35ºC over three months, heated in pineapple nectar at a ratio of 38 and in papaya nectar at a ratio of 66, the longest activation times of 15 and 20 minutes, respectively, were observed. The statistical analysis showed that the factors which had the most influence in the activation time of the ascospores were the ratio and the production temperature of ascospores.